Estudo Experimental e de Simulação por CFD de Escoamentos em Seções Anulares - Vieira Neto, José Luiz (2011)
The increasing activity of oil and gas extraction in deep water has stimulated several studies to solve problems encountered in drilling wells. During the drilling operation, a fluid (drilling mud) is pumped through the column to the bottom, carrying to the surface the drill cuttings generated, through the annular space formed between the column and the borehole wall. In this type of flow may appear a kind of hydrodynamic instability characterized by the appearance of toroidal vortices. This type of instability (Taylor-Couette) may profoundly alter the pressure drop of the flow, the shear stress at the borehole wall and the ability of carrying the solids. Moreover, during the process of drilling a well it is necessary promotes the well cementing and coating to provide a mechanical support, as well as, to isolate it from different rock formations traversed. For this step to be successful, the drilling mud must be completely removed from the annular space, and this removal may be impaired in wells which have varying eccentricity along the tube. Due to high costs of correction transactions and loss of drilling time, it is crucial to predict the mud flow around the annular. The effects of this variation of the eccentricity have not been much discussed in the literature, and they may have great influence on the displacement of the mud in the annular space. As an initial phase of work, numerical simulations were performed to study the flow and the emergence of Taylor- Couette instabilities in a concentric annular section, in order to compare them with literature data. Numerical simulations were developed in annular periodic sections, concentric and eccentric (E = 0.5) in order to obtain average profiles of axial and tangential velocities using different turbulence models, aiming at a comparison of simulated results with experimental data from literature. Later, it was made an experimental study and simulation to assess the effect of internal axis rotation on the pressure drop in the flow of non-Newtonian fluids (aqueous solutions of xanthan gum and carboxymethyl cellulose with 0.2% by weight) in a section annular concentric and the other with fixed eccentricity (E = 0.75). Finally, it was elaborated an experimental design (3k) with four variables, such as, xanthan gum concentration (0.05%, 0.10% and 0.15% by weight), eccentricity (0.0, 0.23 and 0.46), fluid flow rate (5, 7 and 9 m3/h) and internal rotation axis (0, 100 and 200 rpm). Following this planning, experimental data of pressure drop were collected, as well as, numerical simulations (CFD) in periodic annular sections to get results of axial velocity, in order to evaluate the effect of variable eccentric rotation on the fluid dynamics of non-Newtonian flows in annular spaces.